Comparison of Tooth Shade Colour Recorded Using Digital Single Lens Reflex Camera and Mobile Cameras with Manually Adjusted Parameters - Bhat, Vidya S.; Shetty, SanathKumar; Syed, Khizer Ishaquddin; Razdan, Sanha (Journal of evolution of medical and dental sciences, 2021)
BACKGROUND Visual selection by using shade guides is the most common but also the most subjective technique, influenced by factors such as the age of the observer and eye fatigue. Digital imaging provides a practical and consistent method of determining tooth colour. A suitable alternative for DSLR cameras may be a mobile phone camera. Recent smart phones have manual control which helps to manually adjust parameters. Female patients usually use lipstick, which may alter the tooth colour perception, but there is no clinical evidence showing the effect of lipstick on tooth shade. The purpose of this study was to evaluate the reliability of using phone camera and the effect of lipstick on the shade of the tooth. METHODS This study was conducted on 11 female individuals within the age of 18 - 25 years. Eight photographs were made of all 11 participants, using 3 different smart phone cameras and Nikon D3400 DSLR camera with twin flash and cross-polaroid filter was used as the control group. The parameters of all the cameras were standardized for every image. All digital photographs were evaluated with a Digital Colour Meter software, which gave the parameters in the RGB colour codes and CIE L, a*b* colour space. RESULTS There was no statistically significant difference in the L* and R* values between the control and the smartphone camera groups. There was no statistically significant difference in L* and R* values before and after applying lipstick in all the groups. There was no significant difference in L* and R* values in all the groups before and after applying lipstick. CONCLUSIONS Recent smartphone cameras with manually adjusted parameters including unprocessed or RAW images can be used as a reliable tool for shade matching. Shade matching can be done even after applying lipstick, as there was no difference seen in this study. KEY WORDS Esthetics, Shade, Lipstick, Spectophotometer, Shade